The Use of Game-Based Learning Models with Mystery Word Games to Improve Learning Outcomes of 5th Grade Elementary School Students - Nora Fatikha Asyrofia; Ismi Rahmatus Salisa; Anggitia Cempaka Putri; Rohmatul Hasana; Laura Adhi Pramadhika Branigan; Prihatin Sulistyowati (PUSAKA: Journal of Educational Review, 2026)
This classroom action research aims to improve the learning outcomes and motivation of 5B grade students of SDN Bandung Rejosari 4 through the application of the Game Based Learning model with the Mystery Words game. The research was conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The results of the study showed a significant increase in student learning outcomes. The class average score increased from 61 in the pre-cycle to 75.8 in Cycle I, and reached 81.6 in Cycle II. The highest student score increased from 85 to 90, and then 95. Meanwhile, the lowest score also increased from 20 in the pre-cycle to 45 in Cycle I, and rose to 60 in Cycle II. Furthermore, students' learning motivation also showed an increase, from the "Sufficient" category with an average score of 60.25 in the pre-cycle, to the "Good" category with a score of 72.46 in Cycle I, and then to the "Very Good" category with a score of 85.71 in Cycle II. These findings indicate that the Game-Based Learning model with the Mystery Words game is effective in improving student learning outcomes and motivation.